2019
DOI: 10.15359/ru.33-1.6
|View full text |Cite
|
Sign up to set email alerts
|

Estudio bioprospectivo, actividad antibiótica y antioxidante del exocarpio del fruto de santol (Sandoricum koetjape)

Abstract: Con el fin de evaluar las principales propiedades antioxidantes y antibióticas del exocarpio del fruto de Santol (Sandoricum koetjape), se realizó una bioprospección sobre este, así como una caracterización del contenido de polifenoles totales y proantocianidinas. Para lo anterior, al material seco y molido del exocarpio se le realizaron diferentes pruebas cuantitativas y fraccionamientos cromatográficos con diversas resinas, con el propósito de obtener metabolitos puros o mezclas de ellos más concentrados. La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…We followed our previously published protocol (Mesén‐Mora et al, 2019 ) with minor modifications. Two microliters of a 0.1 mg/mL solution of 4‐(Dimethylamino) cinnamaldehyde (DMAC, obtained from Merck KGaA, Darmstadt, Germany), and 70 μL of each plant extract (as described above) were mixed into a microplate well.…”
Section: Methodsmentioning
confidence: 99%
“…We followed our previously published protocol (Mesén‐Mora et al, 2019 ) with minor modifications. Two microliters of a 0.1 mg/mL solution of 4‐(Dimethylamino) cinnamaldehyde (DMAC, obtained from Merck KGaA, Darmstadt, Germany), and 70 μL of each plant extract (as described above) were mixed into a microplate well.…”
Section: Methodsmentioning
confidence: 99%
“…The exact nature of the antioxidant molecules has not been determined but another study reported the antioxidant activity of several flavonoids, such as quercetin-4′-glucoside and luteolin-7β-D-glucopyranoside contained in a leaf extract of S. koetjape (Hamzah et al, 2020). The presence of antioxidant and antibacterial proanthocyanidins (polyphenols) in santol fruits has also been reported (Mesén-Mora et al, 2019).…”
Section: Antioxidant Produc Ts From Fru Itsmentioning
confidence: 99%
“…Inhibition of bacterial growth has been reported with crude extracts of S. koetjape (Dira Swantara and Ciawi, 2012; Abd Azziz et al, 2013; Mesén‐Mora et al, 2019), in particular with a leaf ethanolic extract active against Staphylococcus aureus and Escherichia coli (Nogodula et al, 2013; Bajon et al, 2019). Recently, an aqueous extract of S. koetjape has been found to inhibit the growth of the colibactin‐producing Escherichia coli strain ATCC 25922.…”
Section: Antibacterial Compoundsmentioning
confidence: 99%